Investigation of thickness and wax content of wax deposits in polyethylene pipe using a flow loop. Issue 1 (6th October 2020) - Li, Rongbin; Huang, Qiyu; Zhang, Dongxu; Zhu, Xiangrui; Shan, Jinxu; Li, Zhimin
Abstract: In this study, the thickness and wax content of wax deposits were found to be thinner and lower in the polyethylene (PE) pipe than in the stainless steel (SS) pipe using a flow loop apparatus. The diffusivity of wax, radial thermal gradient, and wax precipitation rate in the PE and SS pipes were calculated and compared. It was found the diffusivity of wax in the PE pipe was higher and tended to enhance the wax deposition in the PE pipe, while the radial thermal gradient and wax precipitation rate were lower in the PE pipe and had the opposite effects. These factors are shown to be comparable with each other and the effect of the thermal gradient dominates the mass flux of wax from bulk to the oil‐deposit interface and into the deposits finally, thus causing differences in thickness and wax content of deposits between the PE and SS pipes.